Effect of exogenous postharvest application with thyme and cinnamon oils on quality and storability of cherry tomato - El-Sayed, Sayed F.; Atress, Amal. S.; Mahmoud, Abdel Wahab M.; Maghraby, Moshera I. F.; El-Mogy, Mohamed M. (International journal of health sciences, 2021)
Cherry tomato are classified as perishable fruits that deteriorate vastly after harvest. The use of natural and eco-friendly products, such as essential oils, for preserving the quality of fresh fruits and vegetables is highly demands for the consumers. Thus, the aim of this study was to evaluate the efficiency of exogenous postharvest application with thyme oil (1%), cinnamon oil (1%), and their combination on quality and shelf-life of cherry tomato stored for 28 days at 10°C and 90% RH. The results indicated that both essential oils were able to preserve the quality of cherry tomato by reducing weight loss, decay, appearance, and firmness. Additionally, essential oils application conserved total soluble solids, total carbohydrates, and total phenolic compounds. Lycopene and carotene contents were decreased by essential oils application. In conclusion, the application of both essential oils could be effective in maintain the quality and increase the shelf-life of cherry tomato during refrigerated storage.